Dynamic Analysis of the Gear Transmission System of High-speed Trains Based on IHBM - Chen Zhan; Zhang Jianchao; Hu Yufei; Wang Jun (Jixie chuandong)
In order to grasp the dynamic characteristics of the gear transmission system of high-speed trains under the torque excitation of the driving end and the load end, the pure torsional vibration model of the gear transmission system of high-speed trains is established. The analytical solution of the system under the torque excitation of the driving end and the load end is obtained by using the incremental harmonic balance method (IHBM). The rationality of IHBM is verified by comparing with the numerical solution of the system. By drawing the frequency response curve of the system, the influence of the change of the main parameters in the torque excitation of the driving end and the load end on the dynamic characteristics of the system is analyzed. The results show that there are several high-order super harmonic resonance regions, amplitude jumps, one or more multi-valued solution regions and other nonlinear characteristics in the system under the parameter changes of the driving end and the load end torque excitation. The research results have a unique reference value for in-depth analysis of the dynamic characteristics of the gear transmission system of high-speed trains under the torque excitation of the driving end and the load end.